Penerapan Metode Clustering Kecemasan Anak Terhadap Bullying - Setia Ningsih; Yani Maulita; Husnul Khair (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
Bullying is a verbal or non-verbal bullying activity through the media (cyber bullying) or directly, carried out by a child or group of children against other children. Aggressive behavior such as bullying among teenagers results in problems such as anxiety. The problem at SMKN 2 Binjai in 2024 is the difficulty of identifying children's anxiety about bullying disorders because there is no strong reference as evidence for cases of bullying carried out by perpetrators against victims. So research is needed to cluster gender, type of bullying and children's anxiety levels, with many parties still not monitoring children's activities enough to see how big the impact is on children who experience bullying. The aim of this research is to determine gender, type of bullying and different levels of anxiety among children who experience bullying. Based on the results of grouping bullying cases using the K-Means algorithm, 3 clusters and 3 iterations were obtained, where cluster 1 contained 9 data. , cluster 2 has 4 data and cluster 3 has 7 data, so it can be concluded that bullying cases tend to occur in women who experience types of bullying in the form of cyber and psychological with a mild level of anxiety.